Analysis of the concentration of vitamin E in erythrocytes of patients with celiac disease - Romańczuk, Bartosz; Szaflarska-Popławska, Anna; Chełchowska, Magdalena; Hozyasz, Kamil K. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction: Consumption of gluten proteins leads to an enteropathy characterised by lymphocytic infiltration of mucous membrane, crypts hypertrophy, and atrophy of villi. Enteropathy leads to disturbances in the immune system as well as secondary deficiency of vitamin E. Aim: Analysis of the concentration of vitamin E in erythrocytes of patients with celiac disease. Material and methods : Three experimental groups were distinguished among 77 patients with histologically confirmed celiac disease (mean age: 17 years): those who strictly respected gluten-free diet (group I, n = 48), patients breaking dietary recommendations (group II, n = 22), and those with newly diagnosed disease (group III, n = 7). Additionally, a control group consisting of healthy individuals with negative serological markers of celiac disease was formed (group IV, n = 20). Vitamin E concentration was determined by high performance liquid chromatography with ultraviolet detector. Results : Significantly lower average concentration of vitamin E was demonstrated in erythrocytes in all examined groups of patients with celiac disease compared to the control group. Among the patients with celiac disease, the highest average concentration of vitamin E in erythrocytes was observed in the group who respected the gluten-free diet, a little lower in patients who violated dietary recommendations, and lowest among patients with newly diagnosed disease. These relationships, however, were not statistically significant. Conclusions : Patients with celiac disease are at risk of vitamin E deficiency irrespective of their diet. Vitamin supplementation should be considered in their case, especially immediately after diagnosis of the disease and in case of breaking a gluten-free diet regime.